Nanotechnology-based strategies for berberine delivery system in cancer treatment: pulling strings to keep berberine in power - Iqbal, Muhammad Javed; Quispe, Cristina; Javed, Zeeshan; Haleema Sadia; Qadri, Qamar Raza; Raza, Shahid; Salehi, Bahare; Martins, Natália Cruz; Abdulwanis Mohamed, Zeinab; Jaafaru, Mohammed Sani; Abdull Razis, Ahmad Faizal; Sharifi-Rad, Javad (Frontiers Research Foundation, 2021)
Cancer is a multifactorial disease characterized by complex molecular landscape and altered cell pathways that results in an abnormal cell growth. Natural compounds are target-specific and pose a limited cytotoxicity; therefore, can aid in the development of new therapeutic interventions for the treatment of this versatile disease. Berberine is a member of the protoberberine alkaloids family, mainly present in the root, stem, and bark of various trees, and has a reputed anticancer activity. Nonetheless, the limited bioavailability and low absorption rate are the two major hindrances following berberine administration as only 0.5% of ingested berberine absorbed in small intestine while this percentage is further decreased to 0.35%, when enter in systemic circulation. Nano-based formulation is believed to be an ideal candidate to increase absorption percentage as at nano scale level, compounds can absorb rapidly in gut. Nanotechnology-based therapeutic approaches have been implemented to overcome such problems, ultimately promoting a higher efficacy in the treatment of a plethora of diseases. This review present and critically discusses the anti-proliferative role of berberine and the nanotechnology-based therapeutic strategies used for the nano-scale delivery of berberine. Finally, the current approaches and promising perspectives of latest delivery of this alkaloid are also critically analyzed and discussed.